Soluble Oligomers of the Pore-forming Toxin Cytolysin A from Escherichia coli Are Off-pathway Products of Pore Assembly - Roderer, Daniel (J Biol Chem, 2016)
The α-pore-forming toxin Cytolysin A (ClyA) is responsible for the hemolytic activity of various Escherichia coli and Salmonella enterica strains. Soluble ClyA monomers spontaneously assemble into annular dodecameric pore complexes upon contact with membranes or detergent. At ClyA monomer concentrations above ∼100 nm, the rate-limiting step in detergent- or membrane- induced pore assembly is the unimolecular reaction from the monomer to the assembly-competent protomer, which then oligomerizes rapidly to active pore complexes. In the absence of detergent, ClyA slowly forms soluble oligomers. Here we show that soluble ClyA oligomers cannot form dodecameric pore complexes after the addition of detergent and are hemolytically inactive. In addition, we demonstrate that the natural cysteine pair Cys-87/Cys-285 of ClyA forms a disulfide bond under oxidizing conditions and that both the oxidized and reduced ClyA monomers assemble to active pores via the same pathway in the presence of detergent, in which an unstructured, monomeric intermediate is transiently populated. The results show that the oxidized ClyA monomer assembles to pore complexes about one order of magnitude faster than the reduced monomer because the unstructured intermediate of oxidized ClyA is less stable and dissolves more rapidly than the reduced intermediate. Moreover, we show that oxidized ClyA forms soluble, inactive oligomers in the absence of detergent much faster than the reduced monomer, providing an explanation for several contradictory reports in which oxidized ClyA had been described as inactive.